Student Final Project Recommendation System Model Using Case-Based Reasoning (CBR) Method - Abdus Salam; Fathurrahmad Fathurrahmad (Jurnal Mantik, 2021)
The purpose of this study is to develop a student final project recommendation system model that can be used to improve the quality of final assignments in universities, especially AMIK Indonesia, and compare it with similar applications currently used. Agile Development Methods (ASD) is used in software development where this method is widely used for software development because it can produce system requirements data that is more descriptive and easy to implement into software. The researcher also uses the Case-Based Reasoning algorithm, which will later be implemented as the basic concept of developing a recommendation system prototype. The results of the study found that; 1) In knowing the topic or research theme in the student's Final Project with an expert system, it can be seen from the themes and sub-themes and valid calculations are carried out in helping students to quickly find out the research title for the final project, 2) By applying the Case-Based Reasoning method in detecting research topics or themes at AMIK Indonesia can produce valid calculations that are the same as manual calculations so that the selection process can be carried out quickly and accurately, and 3) in designing this application it consists of the main menu page, a list of research topics, FAQs and about applications using PHP, ReachJS and MySQL programming languages ??as data processors in the recommendation of a student's final project